Harry S. Truman - Cannarella, Deborah (Minneapolis, Minn. : Compass Point Books, 2003)
A biography discussing the personal life, education, and political career of the thirty-third President of the United States, Harry S. Truman.
"The best of my ability" -- Raised in Independence -- Learning to lead -- Mr. President -- The hardest decision -- "The buck stops here" -- Mr. Citizen.
Includes bibliographical references and index.
0780
Keywords: Truman, Harry S. -- 1884-1972; Presidents -- United States; Presidents; United States -- Politics and government -- 1945-1953